2017
DOI: 10.1159/000460240
|View full text |Cite
|
Sign up to set email alerts
|

Strategies and Outcomes of Repeat Mitral Valve Interventions after Failed MitraClip Therapy

Abstract: Percutaneous mitral valve repair (PMVR) with the MitraClip system (Abbott Vascular, Santa Clara, CA, USA) is a valid therapeutic option for patients with severe mitral regurgitation (MR) deemed to be at high or prohibitive surgical risk. Despite the reassuring data on efficacy and long-term durability of the procedure, the proportion of patients with residual or relapsing severe MR after MitraClip therapy is not negligible. In light of the detrimental prognostic impact of severe MR, repeat interventions are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In 2007, the percutaneous mitral valve repair via the MitraClip system was introduced in clinical use for high-risk surgical patients [5, 6]. In these high-risk patients, percutaneous mitral valve intervention showed effective reduction of mitral regurgitation [7]. Several studies reported good short-term results after mitral clipping, while others compared mitral valve surgery with MitraClip procedures.…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, the percutaneous mitral valve repair via the MitraClip system was introduced in clinical use for high-risk surgical patients [5, 6]. In these high-risk patients, percutaneous mitral valve intervention showed effective reduction of mitral regurgitation [7]. Several studies reported good short-term results after mitral clipping, while others compared mitral valve surgery with MitraClip procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, a specific challenge will be the result of PASCAL system in mitral valve with severe annular dilatation, for which MitraClip alone without annuloplasty did not showed satisfactory long-term results (15) and for which a combined therapy with multiple devices could be warranted (16). Addressing the theme of failure after TMVR, another point to determine will be the possibility to perform a repeat PASCAL procedure with respect to the mitral valve gradient in case of mitral regurgitation recurrence (17).…”
Section: Editorialmentioning
confidence: 99%